Differentiation of Fibroblasts Into Myofibroblasts in the Arachnoid Membrane of Moyamoya Disease. Issue 11 (30th August 2022) - Yamamoto, Shusuke; Yamamoto, Seiji; Akai, Takuya; Sasahara, Masakiyo; Kuroda, Satoshi
Abstract : Background: Moyamoya disease (MMD) is a very specific disorder in terms of spontaneous development of extracranial-to-intracranial collateral circulation through the dura mater, but the underlying mechanisms are unclear. This study aimed to investigate the role of the arachnoid membrane in this unique angiogenesis in MMD. Methods: A piece of arachnoid membrane and 1- to 2-mL cerebrospinal fluid were simultaneously harvested during surgery from 26 patients with MMD. The specimens were also collected during surgery as the controls from 6 patients with atherosclerotic carotid artery diseases. The arachnoid membrane was subjected to immunohistochemistry and the cerebrospinal fluid was used to measure the concentration of cytokines using ELISA. Results: The number of cells positive for PDGFR (platelet-derived growth factor receptor) α was significantly higher in MMD than in the controls (5.4±3.1 versus 2.3±2.1 cells/field; P =0.02). The results were same in PDGFRβ-positive cells (10.1±4.6 versus 4.8±2.8; P=0.01) and α-SMA (alpha-smooth muscle actin)–positive cells (8.8±3.1 versus 2.0±2.5; P<0.01). On multicolor immunofluorescence, 80.5±15.6% of cells positive for PDGFRα in MMD also expressed α-SMA, being significantly higher than 14.6±7.2% in the controls ( P <0.01). The density of collagen in the arachnoid membrane was significantly higher in MMD than in the controls (60.3±15.0% versus 40.1±15.3%; P <0.01). In MMD, advanced disease stage was significantly associated with a larger number of α-SMA–positive cells in the arachnoid membrane ( P =0.04). On ELISA, the cerebrospinal fluid concentrations of bFGF (basic fibroblast growth factor), HGF (hepatocyte growth factor), and TGF (transforming growth factor)-β1 were significantly higher in MMD than in the controls. Conclusions: Based on these findings, MMD may elevate the concentrations of angiogenic factors in the cerebrospinal fluid and then promote the proliferation of fibroblasts in the arachnoid membrane and their differentiation into myofibroblasts, which may, in turn, enhance the production of collagen essential for spontaneous collateral formation across the arachnoid membrane.